ANALISIS AKSIOLOGI PENDIDIKAN ISLAM DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK PPTQ AL HUSNA BAKI - As'adatun niswah; Mujiburrahman (Jurnal Binagogik, 2026)
Scholarly discussions have frequently addressed moral cultivation within pesantren settings. Nevertheless, axiological interpretations of santri formation at PPTQ Al Husna Baki have received relatively little attention. This inquiry investigates how value-oriented religious pedagogy shapes santri dispositions and maps the principles embedded in their routine communal activities. A naturalistic single-site design with a descriptive-interpretive orientation was adopted. The information sources comprised a religious-studies instructor, several ustadzah, and female administrators selected according to the relevance of their knowledge. Empirical material was generated from in-depth conversations, direct field engagement, and the examination of institutional records. It was subsequently processed by isolating essential information, organizing recurring patterns, and formulating interpretive inferences. The findings reveal that axiological commitments are enacted through instructional activities, structured routines, exemplary conduct, and consolidation of a pesantren ethos rooted in religious principles. These mechanisms strengthen piety, orderliness, integrity, accountability, self-reliance, and social sensitivity among santri. This inquiry broadens discussions of Islamic educational axiology by demonstrating the formative significance of consistently embedding religious principles in institutional routines and interpersonal practices.